An Oropharyngeal Accessory Tragus in a Young Patient With Conductive Hearing Loss - Tiffany Husman; Tania Benjamin; Evan J. Patel; Naoki Akanuma; Anastasiya Pigal; Yew Song Cheng (Clinical Case Reports)
ABSTRACT In this report, we describe the first reported case of an oropharyngeal accessory tragus in a 20‐year‐old female presenting with moderate to severe left‐sided conductive hearing loss. This case shares rare developmental anomalies to consider when diagnosing oropharyngeal masses that highlight the intricate embryological development of the head and neck region.